Altruism in networks: the effect of connections. - Curry, O; Dunbar, R (2011)
Why are individuals altruistic to their friends? Theory suggests that individual, relationship and network factors will all influence the levels of altruism; but to date, the effects of social network structure have received relatively little attention. The present study uses a novel correlational design to test the prediction that an individual will be more altruistic to friends who are well-connected to the individual's other friends. The result shows that, as predicted, even when controlling for a range of individual and relationship factors, the network factor (number of connections) makes a significant contribution to altruism, thus showing that individuals are more likely to be altruistic to better-connected members of their social networks. The implications of incorporating network structure into studies of altruism are discussed.